Pangenome analysis of Liriodendron reveals presence/absence variations associated with growth traits - Hainan Wu; Siqi Chen; Jing Wang; Yaxian Zong; Lichun Yang; Chunfa Tong; Huogen Li (BMC Plant Biology)
Abstract Beyond single nucleotide polymorphisms (SNPs), gene presence/absence variation (PAV) plays a crucial role in elucidating species’ genetic diversity, uncovering the genetic basis of key traits, and advancing molecular marker-assisted breeding in plants. In this study, we constructed a pangenome of Liriodendron based on 24 accessions. Comparative analysis with the reference genome revealed 116 Mb of non-reference sequences and obtained 32,773 genes, including 3,558 novel genes. We subsequently employed resequencing data from 247 Liriodendron genotypes to identify PAVs, comprising 13,779 core genes and 18,179 dispensable genes. To further assess PAV applicability, a genome-wide association study (GWAS) was conducted to link gene PAVs with growth traits in hybrid Liriodendron, and identified 14 candidate genes associated with these growth traits above. Additionally, gene PAVs appeared to predominantly contribute to heterosis in growth traits, displaying a dominant expression pattern when comparing leaf, shoot, and phloem tissues of strong and weak heterotic combinations. Additionally, two key candidate genes, Litul.02G164100 and Litul.01G057400, exhibit high parental expression patterns consistent with hybrid vigor in strong heterotic combinations of leaf and shoot tissues. Altogether, this study expands the Liriodendron genomic dataset, identifies candidate genes linked to growth traits, and provides insights into their heterotic mechanisms in hybrid Liriodendron.